Enhancing Sustainable Tourism through Training and Development in India's Public Sector Banks: Impacts on Employee Retention and Satisfaction in Green Financing Initiatives - Abhishek Kumar Singh,; Dr. Shalu Agarwal, (AG Volumes, 2026)
This study looks into green finance initiatives and sustainable tourism education on the satisfaction and retention of staff in government-owned banks in Madhya Pradesh in India. The research analyzes the correlations of the training exposure, perceived integration of sustainability practices, and employee retention factors on the basis of primary data on 40 bank employees in the form of correlation analysis, multiple regression, one-way ANOVA, factor analysis, chi-square tests, and logistic regression. The results indicate the green finance workshop as the most significant indicator of employee happiness in addition to strong positive relations in other significant areas. The satisfaction demonstrated significant differences depending on the experience, with the workers in higher levels of experience being more satisfied with sustainability programs. According to gender statistics, more female workers were subjected to advanced training classes. In addition, logistic regression revealed that the probability of high retention was significantly increased by support of the management and quality of training. The outcomes of the study reveal that when staff retention and satisfaction is encouraged with a concentration of training - in green finance and sustainable tourism, it strengthens the role of the government banks to enhance sustainable development. They include improved mechanisms of management support and gender-equal rules on participation and training based on experience. The study contributes to the small existing pool of empirical literature on the interaction between banking and tourism and sustainability in India.